2018
DOI: 10.1111/ajt.14513
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for donor-derived IL-22 in cutaneous chronic GVHD

Abstract: Graft-versus-host disease (GVHD) is the major cause of nonrelapse morbidity and mortality after allogeneic stem cell transplantation (allo-SCT). Prevention and treatment of GVHD remain inadequate and commonly lead to end-organ dysfunction and opportunistic infection. The role of interleukin (IL)-17 and IL-22 in GVHD remains uncertain, due to an apparent lack of lineage fidelity and variable and contextually determined protective and pathogenic effects. We demonstrate that donor T cell-derived IL-22 significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Yet, as in IBD, there are also some preclinical results that tell a cautionary tale. Specifically, one study demonstrated that inflammation, skin epidermal thickness, and fibrosis were all reduced when IL-22 was neutralized in a model of cutaneous GVHD (Gartlan et al, 2018), assigning a disease-promoting role to IL-22 during chronic inflammation. Such a role would be consistent with other observations of a disease-promoting role of IL-22 in the skin.…”
Section: Gvhdmentioning
confidence: 99%
“…Yet, as in IBD, there are also some preclinical results that tell a cautionary tale. Specifically, one study demonstrated that inflammation, skin epidermal thickness, and fibrosis were all reduced when IL-22 was neutralized in a model of cutaneous GVHD (Gartlan et al, 2018), assigning a disease-promoting role to IL-22 during chronic inflammation. Such a role would be consistent with other observations of a disease-promoting role of IL-22 in the skin.…”
Section: Gvhdmentioning
confidence: 99%
“…In a consecutive step activated B-cells can promote tissue injury via antibody and cytokine production and release, leading to the clinical manifestations of cGVHD ( Figure 1A, step 4). IgG-induced macrophage activation may contribute to cGVHD via secretion of pro-inflammatory cytokines such as IL-6 and IL-22 22 , which maintain inflammation. Tissue stiffness in cGVHD can be enhanced by copious Ig production and deposition together with fibroblast-derived extracellular matrix molecules including collagen and proteoglycans (Figure 1A, step 4).…”
Section: The Role Of B-cell In Cgvhd Based On Findings In Micementioning
confidence: 99%
“…There is also a growing focus in the field in identifying cellular biomarkers of this disease. This work has been driven by detailed flow cytometric evaluation of the T-and B-cell subpopulations driving both acute and chronic disease, [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] as well as increasing use of systems-based transcriptomic approaches to identifying the pathways associated with GVHD, both in preclinical models and clinical samples. 50, [103][104][105][106][107] This work is identifying a new cohort of targetable pathways for GVHD control, many of which are amenable for clinical translation.…”
Section: Postneutrophil Engraftmentmentioning
confidence: 99%